Masonic rites and wrongs an examination of Freemasonry - Tsoukalas, Steven, 1956- (Phillipsburg, NJ Presbyterian and Reformed, 1995)
Includes bibliographical references and index.
Keywords: Freemasonry -- religious aspects -- Christianity